Mapping Recent Deforestation and Forest Disturbance in Northeastern Madagascar. (March 2013) - Allnutt, Thomas F.; Asner, Gregory P.; Golden, Christopher D.; Powell, George V. N.
We conducted an analysis of deforestation and forest disturbance from 2005-2011 in Masoala National Park, the largest federal protected area in Madagascar. We found that the annual rate of forest change in 2010-2011 within the park (1.27%) was considerably higher than in 2005-2008 (0.99%), and was higher than the most recently published deforestation rate for all of Madagascar. Although deforestation and disturbance immediately following the 2009 coup d'état were lower than in the other time periods analyzed, the longer-term increase in forest change over the study period corroborates recent ground-based accounts of increased illegal activities in national parks, including logging of precious hardwoods. We also analyzed forest disturbance patterns in relation to rivers and travel distance from permanent villages. Forest disturbances were significantly closer to rivers than expected by chance, and 82% of disturbance was within the mean maximum travel distance to villages surrounding the park. Both results strongly indicate that most of the mapped disturbance in the study area is anthropogenic, despite two cyclones during the study period. High-resolution forest monitoring ensures that forest change statistics accurately reflect anthropogenic disturbances and are not inflated by forest losses resulting from natural processes.